Psychological Analysis of the Main Character in the Novel Asmarani by Suparto Brata - Istiqomah, Roihanah (Abjad Journal of Humanities & Education, 2024)
The psychological conditions experienced by a person are different, one of the Javanese novels that discusses character psychology is the novel Asmarani by Suparto Brata. This novel tells the story of the main character named Asmarani who was left by her biological mother and then adopted by the Nataran family, while still in elementary school she had an unnatural crush on her teacher who was not like a teacher to his student. This study aims to analyze the psychology of the main character, describe the character of the main character contained in the novel Asmarani by Suparto Brata. This research uses a literary psychology approach using Sigmund Freud's psychoanalysis theory. This research method is descriptive qualitative whose data are phrases, words, and sentences in the novel. The results of this study indicate that there is a psycholoical form of the main character consisting of Id, Ego, and Superego. This research is expected to be able to provide a new face and positive implications in the research of Javanese-language psychological novels.